Framework for creating storytelling materials to promote African American/Black adult enrollment in research on Alzheimer's disease and related disorders. Issue 1 (11th September 2020) - Robinson, Renã A. S.; Williams, Ishan C.; Cameron, Judy L.; Ward, Keisha; Knox, Melissa; Terry, Melita; Tamres, Lisa; Mbawuike, Uchenna; Garrett, Marita; Lingler, Jennifer H.
Abstract: Introduction: African American/Black adults are severely underrepresented in basic, clinical, and behavioral research studies in Alzheimer's disease and related disorders (ADRD). Innovative, evidence‐based, and culturally salient strategies can maximize the recruitment of African American/Black adults into ADRD research. Methods: We conducted and analyzed semi‐structured interviews to capture the research participation stories of African American/Black participants and study partners from the University of Pittsburgh's Alzheimer's Disease Research Center. The themes and messaging principles generated through this process informed the development of video‐ and text‐based materials that were evaluated for community member acceptance using focus groups. Results: Focus group individuals (N = 36) generally favorably rated the video and text materials, characterizing them as "interesting, " "realistic, " and "convincing." Discussion: Capturing the narratives of African American/Black research participants is a critical component to developing culturally relevant materials for broader dissemination and is essential to advancing beyond information‐only recruitment approaches, which tend to rely disproportionately on negative messages.